Aligning Institutional Syllabuses with National Curriculum Goals in English Language Education - Ahmad Rangga Ary Saputra; Anggi Lisna Wati; Eka Nugraha Wardana; Kalayo Hasibuan (MAN 4 Kota Pekanbaru, 2026)
The alignment between institutional syllabuses and national curriculum goals is essential for ensuring coherence, educational quality, and effective learning outcomes. This study examines how English Language Education programs at the State Islamic University of Sultan Syarif Kasim Riau align their institutional syllabuses with national curriculum standards, particularly the Kurikulum Merdeka. Employing a qualitative descriptive research design, data were collected through document analysis of institutional syllabuses and semi-structured interviews with lecturers and curriculum coordinators. The findings indicate partial alignment, in which learning outcomes generally reflect national competencies, while inconsistencies persist in the implementation of instructional strategies and assessment practices. Key challenges include limited understanding of the national curriculum framework, insufficient structured professional development, and minimal collaborative curriculum planning. The study identifies curriculum mapping, outcome-based syllabus design, and collaborative professional development as strategic approaches to strengthening alignment. It concludes that sustained institutional commitment, continuous evaluation, and faculty collaboration are essential for achieving coherent and meaningful curriculum implementation in English language education.